EVALUATION OF RE-USED HPTLC PLATE FOR QUALITATIVE AND QUANTITATIVE ANALYSIS - Lestyo Wulandari (Universitas Gadjah Mada, 2006)
The eficiency chromatography of HPTLC plate is better than conventional TLC plate but it more expensive. Due to the higher price of HPTLC plate compare to conventional TLC plate, the application of